Combined Subcutaneous-Intranasal Immunization With Epitope-Based Antigens Elicits Binding and Neutralizing Antibody Responses in Serum and Mucosae Against PRRSV-2 and SARS-CoV-2 - Fragoso-Saavedra, Mario; Ramírez-Estudillo, Carmen; Peláez-González, Diana L.; Ramos-Flores, Jorge O.; Torres-Franco, Gustavo; Núñez-Muñoz, Leandro; Marcelino-Pérez, Gabriel; Segura-Covarrubias, María G.; González-González, Rogelio; Ruiz-Medrano, Roberto; Xoconostle-Cázares, Beatriz; Gayosso-Vázquez, Amanda; et al. (Frontiers in Immunology, 2022)
New vaccine design approaches, platforms, and immunization strategies might foster antiviral mucosal effector and memory responses to reduce asymptomatic infection and transmission in vaccinated individuals. Here, we investigated a combined parenteral and mucosal immunization scheme to induce local and serum antibody responses, employing the epitope-based antigens 3BT and NG19m. These antigens target the important emerging and re-emerging viruses PRRSV-2 and SARS-CoV-2, respectively. We assessed two versions of the 3BT protein, which contains conserved epitopes from the GP5 envelope protein of PRRSV-2: soluble and expressed by the recombinant baculovirus BacDual-3BT. On the other hand, NG19m, comprising the receptor-binding motif of the S protein of SARS-CoV-2, was evaluated as a soluble recombinant protein only. Vietnamese mini-pigs were immunized employing different inoculation routes: subcutaneous, intranasal, or a combination of both (s.c.-i.n.). Animals produced antigen-binding and neut1ralizing antibodies in serum and mucosal fluids, with varying patterns of concentration and activity, depending on the antigen and the immunization schedule. Soluble 3BT was a potent immunogen to elicit binding and neutralizing antibodies in serum, nasal mucus, and vaginal swabs. The vectored immunogen BacDual-3BT induced binding antibodies in serum and mucosae, but PRRSV-2 neutralizing activity was found in nasal mucus exclusively when administered intranasally. NG19m promoted serum and mucosal binding antibodies, which showed differing neutralizing activity. Only serum samples from subcutaneously immunized animals inhibited RBD-ACE2 interaction, while mini-pigs inoculated intranasally or via the combined s.c.-i.n. scheme produced subtle neutralizing humoral responses in the upper and lower respiratory mucosae. Our results show that intranasal immunization, alone or combined with subcutaneous delivery of epitope-based antigens, generates local and systemic binding and neutralizing antibodies. Further investigation is needed to evaluate the capability of the induced responses to prevent infection and reduce transmission.